Analyzing the Application of Artificial Intelligence in Monitoring Students Physical Activity within Technology-Enhanced Physical - Butsiarah (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
This study investigates the effectiveness of Artificial Intelligence (AI)-based monitoring tools in improving students' physical activity engagement in technology-enhanced Physical Education (PE) classes. Using a quasi-experimental design, 60 junior high school students were divided into control and experimental groups. The experimental group utilized AI-integrated wearable devices and mobile applications to track daily physical activity, while the control group followed conventional PE methods without AI support. Pre-test and post-test data were collected using standardized physical activity questionnaires and step-count metrics. Results showed a significant improvement in the experimental group's activity levels, with an average increase of 32% in daily step counts (from 4,500 to 5,940 steps, p < 0.05) and a 28% increase in physical activity motivation scores. In contrast, the control group showed minimal changes. The findings demonstrate that AI-based monitoring positively influences students' engagement and awareness of physical activity. The study concludes that AI technologies can serve as effective educational tools in modern PE instruction, although considerations regarding accessibility and teacher training remain essential for broader implementation.